Synthesis, Supramolecular Structure, Antimicrobial and Plant-Growth Regulation Activities of N-Benzoylthiourea - Zhao, Meng-Meng; Dong, Xiu-Yan; Yang, Yu-Hua; Li, Gang; Zhang, Yu-Jie (Asian Journal of Chemistry, 2013)
N-Benzoylthiourea has been synthesized and characterized by elemental analysis, IR and 1H NMR etc. The X-ray crystallography of the compound indicates that the carbonyl group forms an intramolecular hydrogen bond with the N2-H2 group, which forms a six-membered ring (C7/N1/C8/N2/H2/O1) srtucture. Each molecule are linked by the intermolecular N2-H2A...S2 and N4-H4A...S1 hydrogen bonds to form a dimer, adjacent dimers are linked by the intermolecular N1-H1N...S2 and N3-H3N...S1 hydrogen bonds, leading to a hydrogen-bonded netty structure. The results indicated that the N-benzoylthiourea played the important role in plant-growth regulators and may be a potential source of active antimicrobial agents.